2022
DOI: 10.53550/eec.2022.v28i03.045
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vitamin D2 accumulation potential of two edible mushrooms from North-East India

Abstract: Vitamin D is a fat-soluble vitamin that plays an important role in calcium absorption from the intestinecontributing to bone health and many other functions leading to health improvement. There are mainlytwo forms of Vitamin D, namely Vitamin D3 (Cholecalciferol) and Vitamin D2 (Ergocalciferol). Ergocalciferol(Vitamin D2) is a form of Vitamin D found in food, especially mushrooms. Mushrooms contain ergosterolin their cell membrane; exposure to sunlight/ultraviolet (UV) light causes a photochemical reaction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…White Oyster mushroom, Pleurotus florida is a commonly grown mushroom species due to its high nutritional value, ease and low cost of cultivation. Begum, et al [43], reported that Vitamin D2 from fruiting bodies of two Oyster Mushroom species, namely Pleurotus florida and Pleurotus cornucopiae, is quantified using a spectrophotometer at 264nm and it was observed that Vitamin D2 levels varied with different wavelengths used. Both the species, Vitamin D2 levels increased in the UV-B range than in the UV-A range.…”
Section: Mushrooms As a Potential Source Of Dietary Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…White Oyster mushroom, Pleurotus florida is a commonly grown mushroom species due to its high nutritional value, ease and low cost of cultivation. Begum, et al [43], reported that Vitamin D2 from fruiting bodies of two Oyster Mushroom species, namely Pleurotus florida and Pleurotus cornucopiae, is quantified using a spectrophotometer at 264nm and it was observed that Vitamin D2 levels varied with different wavelengths used. Both the species, Vitamin D2 levels increased in the UV-B range than in the UV-A range.…”
Section: Mushrooms As a Potential Source Of Dietary Vitamin Dmentioning
confidence: 99%
“…The level of Vitamin D2 increased to an optimum level at 120 minutes of UV exposure. Vitamin D2 levels obtained from Pleurotus florida and Pleurotus cornucopiae safe and can be used in the preparation of Vitamin D supplements in the future [43].…”
Section: Mushrooms As a Potential Source Of Dietary Vitamin Dmentioning
confidence: 99%